Assessment of adherence with oral anticancer agents in oncology clinical trials: A systematic review. (February 2016) - Bergsbaken, JJ; Eickhoff, JC; Buss, BA; Mably, MS; Kolesar, JM
Background: Despite recommendations for adherence reporting in clinical trials involving an oral anticancer agent, the frequency and methods of adherence reporting are inconsistent. The purpose of this systematic review is to determine the frequency and type of adherence measures used in oncology and hematology clinical trials of oral anticancer agents and their association with study characteristics including quality, cancer type, stage and treatment type. Design: PubMed was searched of all randomized controlled clinical trials assessing self-administered pharmacological interventions in patients with cancer and published over two years, between 1 January 2011 and 31 December 2012 were evaluated. Results: We identified 70 publications in the PubMed database, comprising 45, 118 total patients. Adherence reporting was present in 14 of 70 trials (20%); quantitative reporting was present in three of 70 trials (4%). Method of adherence assessment varied and included medication count, medication diaries and patient self-report. There was no association between adherence reporting and study quality or other study characteristics, although there was a trend towards increased reporting in breast cancer studies, with 46% of the studies reporting adherence ( p  = 0.0621). In a preliminary analysis, hematology studies (mean Jadad score 2.19 ± 1.47) were found to have significantly lower quality when compared to non-hematology trials (mean Jadad score 3.39 ± 1.37, p  = 0.0034). Conclusion: This systematic review demonstrates adherence reporting in clinical trials of oral anticancer agents is infrequent. When reported, adherence was not associated with overall study quality or other study characteristics. Given the potential effects of non-adherence on study power and validity, adherence reporting should be encouraged in oncology and hematology clinical trials.